Policy framing and crisis narratives around food safety in Vietnam - Béné, Christophe; Kawarazuka, Nozomi; Pham, Huong; Haan, Stef de; Tuyen, Huynh; Thanh Thi, Duong; Dang, Chien (SAGE Publications, 2021)
While progress has been made recently in understanding food systems per se, much less is known about policies around those food systems. In this paper, we aim at understanding the food system policy context with the specific objective to look at policy dynamics—defined as the way policy agendas are identified, justified, and framed by decision-makers, and how they interact. Vietnam is used as a case study. Primary data were generated through face-to-face interviews complemented by an online survey. A policy framing approach was used to structure the research. The analysis reveals how the policy agenda is considered by many actors to be only partially evidence-based and highlights the extent to which the state government remains the most powerful actor in the setting of that agenda. The research also reveals the diffusion of the food safety crisis narrative beyond its original technical domain into a larger number of policy framings related to other issues of food systems, thus making it de facto the “center of gravity” of the current agenda on food systems in Vietnam. Yet, a comparison with data from other countries challenges this narrative, and reveals instead how the (legitimate) public concern about food safety is being instrumentalized by certain groups of actors to advance their own agenda. The implication of this “distorted” framing is the risk for the decision-makers to “overfocus” their attention on this short-term issue and lose sight of some other longer-term structural trends such as the emergence of obesity in Vietnamese urban population.